2005
DOI: 10.1111/j.1600-0714.2005.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of oral epithelial cells in oral lichen planus caused by upregulation of BMP‐4

Abstract: Expression of BMP-4 of epithelial cells was higher in OLP than NOM. High concentration of BMP-4 caused an apoptosis of oral epithelial cells in oral mucosa organ culture. Therefore, over-expression of BMP-4 is one causing factor for apoptosis of oral epithelial cells through upregulation of p53, MMP1 and MMP3 in OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 27 publications
0
31
2
2
Order By: Relevance
“…Based on the results of the microarrays and quantitative RT-PCR, it seems clear that expression of MMP-3 in HDFs is more affected than that of MMP-1. BMP-4 was reported to induce the expression of MMP-1 and MMP-3 in oral epithelium (25). However, our results did not confirm this ( Table 1).…”
Section: Discussioncontrasting
confidence: 57%
“…Based on the results of the microarrays and quantitative RT-PCR, it seems clear that expression of MMP-3 in HDFs is more affected than that of MMP-1. BMP-4 was reported to induce the expression of MMP-1 and MMP-3 in oral epithelium (25). However, our results did not confirm this ( Table 1).…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, other studies have shown that the inhibition of BMP signaling by overexpression of Nog under a Krt5 promoter in the epidermis also results in alterations in eyelid epithelial differentiation, and the levels of involucrin and loricrin are reduced (Sharov et al, 2003). Conversely, the addition of Bmp4 to cultured human oral epithelium increases the expression of involucrin (Kim et al, 2006). These studies suggest that BMP signaling regulates the differentiation of suprabasal cells in stratified epithelium.…”
Section: Ectopic Activation Of Bmp Signaling In the Epitheliummentioning
confidence: 71%
“…Additionally, BMP4 is known to induce apoptosis in a p53 (TRP53)-dependent manner in cancer cells as well as oral epithelial cells (Fukuda et al, 2006;Kim et al, 2006;Haubold et al, 2010). p53 tumor suppressor is a transcription factor that induces cell growth arrest and apoptosis (Kerr et al, 1972).…”
Section: Introductionmentioning
confidence: 99%